1996
DOI: 10.1177/1077801296002002004
|View full text |Cite
|
Sign up to set email alerts
|

Male Student-Athletes and Violence Against Women

Abstract: This article examines the relationship between collegiate athletic participation and reported violence against women at Division I institutions. The research is based on the records of 10 judicial affairs offices over a 3-year period from 1991 through 1993. The findings indicate an over-representation of male student-athletes in reports of violence against women (battering and sexual assault). In total, 20 cases of battering and 69 cases of sexual assault are examined. The findings are statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…Additionally, a meta-analysis of studies with college males showed that athletic participation and fraternity membership were both associated with perpetration of sexual assault and with rape-supportive attitudes (Murnen & Kohlman, 2007). The same has been found in the institution of sport, where both collegiate (Crosset et al, 1996; Koss & Gaines, 1993) and professional football players (Benedict, 1997) have been found to perpetrate violence against women at higher rates than men in the general population, although studies generally lack longitudinal analysis and rigorous designs and may suffer from self-selection bias.…”
Section: Introductionmentioning
confidence: 67%
“…Additionally, a meta-analysis of studies with college males showed that athletic participation and fraternity membership were both associated with perpetration of sexual assault and with rape-supportive attitudes (Murnen & Kohlman, 2007). The same has been found in the institution of sport, where both collegiate (Crosset et al, 1996; Koss & Gaines, 1993) and professional football players (Benedict, 1997) have been found to perpetrate violence against women at higher rates than men in the general population, although studies generally lack longitudinal analysis and rigorous designs and may suffer from self-selection bias.…”
Section: Introductionmentioning
confidence: 67%
“…Other rape-prone subcultures may include male athletic teams, the military (O'Toole, 1994), or other groups consisting of male peers (Schwartz & DeKeserdy, 1997). Several researchers have indicated that male student-athletes are more likely to be sexually aggressive and commit sexual assault than other students (Crossett, Benedict, & McDonald, 1995;Crosset, Ptacek, McDonald, & Benedict, 1996;Frintner & Rubinson, 1993;Koss & Gaines, 1993;Murnen & Kohlman, 2007), although there is the suggestion that not all student-athlete teams or communities are equally at risk for committing sexual assault (Humphrey & Kahn, 2000). Some research suggests that certain types of sport teams are more likely to be sexually aggressive, such as contact sports that involve more physical aggression, including football and basketball (Forbes, Adams-Curtis, Pakalka, & White, 2006).…”
mentioning
confidence: 96%
“…Perhaps institutional review boards are more responsive to such studies because these involve only pencil-and-paper "tests" (e.g., questionnaires or surveys) rather than field work that is more intrusive (e.g., observation). In any case, the research on rape occurring within colleges and universities has failed to show that most rapes are the result of the attitudes or beliefs held by athletes and fraternity men (Crosset et al 1996;Koss and Cleveland 1996;McCray 2015).…”
mentioning
confidence: 99%